Planet of the apes (1968) [videorecording (DVD)] - Schaffner, Franklin J.; Heston, Charlton; McDowall, Roddy; Hunter, Kim, 1922-2002; Evans, Maurice, 1901-1989; Boulle, Pierre, 1912-1994 (Twentieth Century Fox Home Entertainment, 2000)
Astronauts crash-land on an unknown planet to find that apes are the dominant, intelligent species.